Glycosylation as a strategic mechanism for measles virus and mumps virus immune evasion - Galvan, Catalina; Ovsyannikova, Inna G.; Kennedy, Richard B. (Frontiers in Immunology, 2025)
Glycosylation of viral surface proteins by host cell factors is one strategy paramyxoviruses employ to evade the host’s immune system during infection. Viral glycosylation thus has the potential for innate and adaptive immune modulation. However, an adequate assessment of the effects glycosylation has on immune recognition and response for two important paramyxoviruses, Measles virus (MeV) and Mumps virus (MuV), is lacking. This review aims to provide a comparison of epitope-site sequence changes in the surface glycoproteins MeV-H, MeV-F, MuV-HN, and MuV-F across different wild type and vaccine strains of measles and mumps. Such changes may alter glycosylation patterns at antigenic sites, thus altering the virus’ efficiency to induce an immune response as well. Further investigation of measles and mumps viral glycosylation studies will aid the development of specific therapeutics that modulate viral glycosylation during immune diseases, viral infections, and oncolytic treatments. Moreover, determining how glycosylation affects measles and mumps immune responses may pave the way for the development of novel vaccine strains for the improved immunogenicity and immune durability of measles and mumps vaccines.